Steady CFD combustion modeling for biomass boilers: An application to the study of the exhaust gas recirculation performance. (1st January 2019) - Gómez, M.A.; Martín, R.; Chapela, S.; Porteiro, J.
Highlights: An efficient CFD model is presented to study biomass combustion systems. The model is applied to the study of EGR in a domestic boiler. Thermal performance and NOx emissions can be improved with direct EGR. Abstract: This work presents an efficient model to simulate the steady operation of biomass boilers and to analyze the thermal behavior of the system in different working scenarios. The model is based on the implementation of calculations on the thermal conversion of biomass in a computational fluid dynamics (CFD) environment to solve the gas phase. The mass, energy and species balances and reactions that take place in the biomass packed bed are introduced in a porous region inside the computational domain of the boiler. The biomass thermal conversion is combined with other submodels, such as radiation transport, gas transport and chemical reactions, to solve the complex combustion phenomena with relatively little computational effort. The model is tested by comparing two different simulations with their respective experimental tests. Parameters relative to the boiler thermal performance and contaminant emissions are compared with reasonably good results. The potential of the model to analyze different operation conditions of a boiler is applied to the theoretical study of the effect of the exhaust gas recirculation (EGR) on the boiler performance and the gas contaminant emissions. For this study, several simulations of a boiler fed with pure oxygen are performed by changing the EGR fraction and the oxygen excess. The results of the study show that the EGR effect can increase the boiler thermal performance, especially for low oxygen excess values. This effect also reduces the NOx emissions for low oxygen excess values. EGR does not seem to have any significant effect on CO emissions.